Chitosan/Sodium Alginate/Velvet Antler Blood Peptides Hydrogel Promoted Wound Healing by Regulating PI3K/AKT/mTOR and SIRT1/NF-κB Pathways - Hao, Mingqian; Peng, Xiaojuan; Sun, Shuwen; Ding, Chuanbo; Liu, Wencong (Frontiers in Pharmacology, 2022)
Skin wound healing is a principal clinical challenge and it is necessary to develop effective alternative treatments. Excessive inflammatory response is linked to delayed healing. This study was the first to report a multi-functional chitosan/sodium alginate/velvet antler blood peptides (VBPs) hydrogel (CAVBPH) and explore its potential mechanism to promote wound healing. The results showed that CAVBPH possessed the desirable characteristics including thermo-sensitivity, antioxidation, antibacterial activity, biosafety, VBPs release behavior, etc., and significantly accelerated skin wound healing in mice. Specifically, CAVBPH treatment enhanced cell proliferation, angiogenesis and extracellular matrix (ECM) secretion, and also relieved inflammation at the wound site compared to PBS-treated group and blank hydrogel scaffold-treated group. Mechanistically, the efficacy of CAVBPH might be related to the activation of PI3K/AKT/mTOR and SIRT1/NF-κB pathways. Overall, CAVBPH seems to be a promising therapy for skin repair, probably relying on the abundant short-chain peptides in VBPs.